Factors associated with the mortality of tilapia (Oreochromis niloticus) due to estreptococcosis produced by Sreptococcus agalactiae in aquaculture farms in the Atiocoyo Irrigation District, El Salvador - Polio-Martinez, M.; Buendía, C.; Vasquez-Jandres, M.; Romero-Rivera , M.; Palacios-Valladares, J.; Vásquez-Hernandez, K.; Perdomo-Ramirez, Y. (Revista Minerva, 2024)
Fish diseases caused by bacteria or parasite infection are important problems hindering tilapia (Oreochromis niloticus) culture. Streptococcosis, due to Streptococcus spp. infection, is one of the main cause of tilapia mortality in tilapia farms. The objective was to identify the factors associated with tilapia mortality due to Streptococcus agalactiae in artisan tilapia farms in the Atiocoyo irrigation district, El Salvador, during march – June, 2022. The presence of S. agalactiae was investigated in fish, water and feed of 28 culture ponds. The serotype of the infecting bacteria was also determined. The bacteria was present only in the fish and not detected in water or feed. PCR analysis indicated that the serotypes responsible for the streptococosis were 1a and III belonging to genes cps 1 aH y cps1a/2/31 in the Polysaccharide Capsule (CPS). Physicochemical pond water parameters were also evaluated. Results of these analyses revealed a relationship between the presence S. agalactiae and dissolved water oxygen, high water temperature and elevated levels of phospahate and ammonia.